2019
DOI: 10.1371/journal.pone.0218166
|View full text |Cite
|
Sign up to set email alerts
|

The contingent use of cell-free fetal DNA for prenatal screening of trisomies 21, 18, 13 in pregnant women within a national health service: A budget impact analysis

Abstract: Objective Non-invasive prenatal testing (NIPT) based on cell-free fetal DNA (cffDNA) is highly accurate in the detection of common fetal autosomal trisomies. Aim of this project was to investigate short-term costs and clinical outcomes of the contingent use of cffDNA for prenatal screening of trisomies 21, 18, 13 within a national health service (NHS). Methods An economic analysis was developed from the perspective of the Italian NHS to compare two possible scenarios fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…In the context of any structural anomaly, including an increased nuchal translucency (>3.5 mm), invasive testing would allow additional diagnostic testing beyond the three main trisomies, including chromosomal microarray 910. The use of NIPT in a high-chance population reduces invasive procedure rates (and their associated costs) and increases aneuploidy detection rates because some women who would not want an invasive test will opt for NIPT 222324…”
Section: Who Should Be Offered Nipt Screening?mentioning
confidence: 99%
“…In the context of any structural anomaly, including an increased nuchal translucency (>3.5 mm), invasive testing would allow additional diagnostic testing beyond the three main trisomies, including chromosomal microarray 910. The use of NIPT in a high-chance population reduces invasive procedure rates (and their associated costs) and increases aneuploidy detection rates because some women who would not want an invasive test will opt for NIPT 222324…”
Section: Who Should Be Offered Nipt Screening?mentioning
confidence: 99%
“…They proposed that women with intermediate risk (defined as 1:11-2500 in that study) could also be offered NIPS 22 . Some researchers suggested that the introduction of NIPS as a second line screening test, conditional to a risk ≥1:1000 from Standard of Care screening, showed a 3% increase in the detection of trisomies, with a 71% decrease in the number of invasive tests performed 23 . Other previous study suggest that the use of risk scores between 1:251 and 1:1000 may be a more cost-effective threshold 24 .…”
Section: Discussionmentioning
confidence: 99%
“…En el panorama internacional también se encontraron estudios similares, como el realizado por Prefumo y cols. (19), que comparó la implementación del cribado contingente con el cribado habitual. Observaron un incremento en la detección de trisomías del 3 % y, al igual que este estudio, se observa una reducción del número de pruebas invasivas (hasta en un 71 %) y una disminución en los costes del 22 %.…”
Section: Análisis De Costo -Efectividad De La Implementación De La Pr...unclassified
“…Analizando el marco económico, parece acertado comentar, según los diversos estudios y con apoyo en los resultados obtenidos en este estudio, que la aplicación de la PPNI supone un ahorro gracias a la disminución de las pruebas invasivas (16,17,19 En cuanto a las limitaciones del estudio, como ya se ha comentado, no se han tenido en cuenta los costes indirectos de las pruebas y, además, hay factores que pueden dificultar su comparación con otros estudios.…”
Section: Análisis De Costo -Efectividad De La Implementación De La Pr...unclassified